2016
DOI: 10.1016/j.ecoser.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Valuing forest ecosystem services and disservices – Case study of a protected area in India

Abstract: This study seeks to estimate the value of forest ecosystem services provided by a protected area in a biodiversity hotspot in India. The novelty of the study rests in that it addresses some of the shortcomings identified in existing literature by also estimating the value of several intangible benefits ignored in most valuation studies as well as estimating the value of disservices of forests such as wild life damages and forest fires, and the added value obtained by forests as compared to from alternative lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 37 publications
1
44
1
1
Order By: Relevance
“…Conversely, the fire regulation ES estimated for Spanish ecosystems (Román et al, 2013) using revealed preferences techniques is much higher (2229 T€ ha −1 on average) than our estimates. Ninan and Kontoleon (2016), using an ESD conceptual approach, reported a value of 2.1 € ha −1 per year (1US Dollar = 0.94€) for the compensation paid by state forest authorities for wildfire damage and the social damage value of carbon emissions by fires, which is much lower than our estimates. Overall, differences found among studies may be partially explained by different valuation methods applied, but also due to different conceptual basis of the assessment and the different Â.…”
Section: Trends In Fire Protection Ecosystem Servicecontrasting
confidence: 81%
See 1 more Smart Citation
“…Conversely, the fire regulation ES estimated for Spanish ecosystems (Román et al, 2013) using revealed preferences techniques is much higher (2229 T€ ha −1 on average) than our estimates. Ninan and Kontoleon (2016), using an ESD conceptual approach, reported a value of 2.1 € ha −1 per year (1US Dollar = 0.94€) for the compensation paid by state forest authorities for wildfire damage and the social damage value of carbon emissions by fires, which is much lower than our estimates. Overall, differences found among studies may be partially explained by different valuation methods applied, but also due to different conceptual basis of the assessment and the different Â.…”
Section: Trends In Fire Protection Ecosystem Servicecontrasting
confidence: 81%
“…Although some efforts have been made to identify potential indicators (Maes et al, 2011;Pettorelli et al, 2017), the inclusion of wildfires in ES-based (or EDS-based) assessment frameworks remains limited. Exceptions include case studies using fire metrics in ES assessment (Azevedo et al, 2011a;Halofsky et al, 2017;Madureira et al, 2013), or econometric approaches to assess the resulting service (Bernués et al, 2014;Madureira et al, 2013;Ninan and Kontoleon, 2016;Parthum et al, 2017;Román et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Forests are also valued for the many recreational benefits they afford, such as viewing wildlife and nature, safari hunting, boating and angling, hiking, etc (Ninan et al 2016). These services are not traded in regular markets and do not have a market price to be used in the economic valuation exercise.…”
Section: Recreationmentioning
confidence: 99%
“…Benefit transfer carries forward measurement errors inherent in any primary study on which it relies, and should not replace methodical and meticulous on-the-ground study. We note, however, that more robust studies often still rely on estimates, approximations, models, simplifications or secondary valuations [68,79]. Meanwhile, local detailed studies in at least some …”
Section: Benefit Transfermentioning
confidence: 99%